An Examination of the Critical success factors of the business process Re-Engineering Implementation Process In Malaysia Domestic Banks And Finance Companies - Khong, Kok Wei (2003)
The aim of this thesis is to examine how the Critical Success Factors of Business Process Re-engineering implementation affect the perceived performances of Malaysian domestic bank and finance companies, and hence to create a perceptual causal relationship model relating these variables.